2022
DOI: 10.3389/fnut.2021.797920
|View full text |Cite
|
Sign up to set email alerts
|

Altered Taste Function in Young Individuals With Type 1 Diabetes

Abstract: Past studies on altered taste function in individuals with type 1 diabetes have yielded inconsistent results. We therefore evaluated taste recognition and possible association with personal and diseases characteristics in young individuals with type 1 diabetes and healthy controls. Taste recognition and intensity for 6-n-propylthiouracil (PROP), quinine, citric acid, sucrose, and sodium chloride were assessed using a filter paper method in 276 participants with type 1 diabetes and 147 healthy controls. Persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The mitochondrial antioxidant enzymes, by counteracting oxidative stress, help maintain a conducive cellular environment within the taste buds, thus preserving taste perception [43]. This is particularly pertinent considering the adverse impact of taste disorders on nutritional intake and the overall quality of life of individuals with DM [13,35]. Our serum findings further enriched our understanding of this mechanism.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The mitochondrial antioxidant enzymes, by counteracting oxidative stress, help maintain a conducive cellular environment within the taste buds, thus preserving taste perception [43]. This is particularly pertinent considering the adverse impact of taste disorders on nutritional intake and the overall quality of life of individuals with DM [13,35]. Our serum findings further enriched our understanding of this mechanism.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, altered taste perception can lead to inadequate nutrition, as individuals may avoid certain foods or consume others in excess, potentially resulting in malnutrition or the exacerbation of obesity, which are both common challenges in diabetic care [34]. Furthermore, taste disturbances may deter patients from adhering to dietary recommendations, which is critical for managing DM and preventing its associated complications [13]. Hence, understanding and addressing neuropathy-induced taste disturbances in individuals with DM not only elucidates a lesser-known complication of this metabolic disorder, but also opens avenues for improving dietary management and overall quality of life for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM-related neuropathy affects nerve conduction, which affect neurotrophins-dependent innervation and impact taste perception. Numerous studies have shown taste impairment in T2DM, but the pathogenesis of such dysgeusia is still unclear (21,22) . This impairment may be due to micro-and macro-vascular complications of hyperglycemia, oxidative damage, reduced growth factor support and oral mucosal inflammation (22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Cozzini et al found reduced corneal nerve fber density in adolescents with T1D compared to healthy control subjects [11]. Yilmaz et al found reduced smell function in 30 children with T1D compared to control subjects, but within the normal ranges [12], and Catamo et al demonstrated impaired taste perception in young individuals (aged 6 to 20 years) with T1D [13]. Te sparse number of studies makes it difcult to conclude whether cranial nerve afection in adolescents with T1D is a problem or not, and studies of adults with T1D have shown contradictory results [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%